Treatment of bleeding episodes in haemophilia A complicated by a factor VIII inhibitor in patients receiving Emicizumab. Interim guidance from UKHCDO Inhibitor Working Party and Executive Committee. Issue 3 (1st June 2018) - Collins, P. W.; Liesner, R.; Makris, M.; Talks, K.; Chowdary, P.; Chalmers, E.; Hall, G.; Riddell, A.; Percy, C. L.; Hay, C. R.; Hart, D. P.
Abstract : Emicizumab is a bispecific antibody that activates FX to FXa in the absence of FVIII. It has been shown to reduce bleeding episodes in people with haemophilia A complicated by a FVIII inhibitor. Despite the protection against bleeds, some breakthrough bleeds are inevitable and these may require additional haemostatic treatment. Emicizumab has been associated with severe adverse events when co‐administered with activated prothrombin complex concentrate. To minimize the risk of adverse events, the UK Haemophilia Centre Doctors' Organisation issues the following updated interim guidance to its Inhibitor Guidelines for managing patients receiving Emicizumab based on the limit published information available in February 2018.